Arsenic trioxide suppresses liver X receptor β and enhances cholesteryl ester transfer protein expression without affecting the liver X receptor α in HepG2 cells. (25th October 2016) - Cheng, Tain-Junn; Lin, Shu-Wen; Chen, Chih-Wei; Guo, How-Ran; Wang, Ying-Jang
Abstract: Chronic arsenic exposure is associated with cerebrovascular disease and the formation of atherosclerotic lesions. Our previous study demonstrated that arsenic trioxide (ATO) exposure was associated with atherosclerotic lesion formation through alterations in lipid metabolism in the reverse cholesterol transport process. In mouse livers, the expression of the liver X receptor β (LXR-β) and the cholesteryl ester transfer protein (CETP) was suppressed without any changes to the lipid profile. The aim of this study was to elucidate whether ATO contributes to atherosclerotic lesions by suppressing LXR-β and CETP levels in hepatocytes. HepG2 cells, human hepatocytes, were exposed to different ATO concentrations in vitro . Cell viability was determined by a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2H-tetrazolium bromide assay. The liver X receptor α (LXR-α), LXR-β, sterol regulatory element-binding protein-1c (SREBP-1c) and CETP protein levels were measured by Western blotting, and their mRNA levels were measured by real-time PCR. Cholesterol efflux was analyzed by flow cytometry. The results showed ATO inhibited LXR-β mRNA and protein levels with a subsequent decrease in SREBP-1c protein levels and reduced cholesterol efflux from HepG2 cells into the extracellular space without influencing LXR-α mRNA and protein levels. CETP protein levels of HepG2 cells were significantly elevated under arsenic exposure. Transfection of LXR-β shRNA did not change CETP protein levels, implying that there is no cross-talk between LXR-β and CETP. In conclusion, arsenic not only inhibits LXR-β and SREBP-1c mRNA and protein levels but also independently increases CETP protein levels in HepG2 cells. Highlights: As2 O3 suppresses LXR-β transcription but not LXR-α expression in HepG2 cells. As2 O3 enhances cholesteryl ester transfer protein (CETP) expression in HepG2 cells. No cross-talk between LXR-β and CETP in the HepG2 cells.